POLITIK PEMAAFAN - Sofia Hayati (Jurnal Studi Agama, 2019)
Forgiveness is often understood as an attitude to overcome negative things and judgment of a guilty person by not denying the pain itself, but with compassion, empathy, and love for those who hurt. Some things to know from forgiveness are what and how forgiveness, stages of forgiveness and forgiveness elements. In the political context, forgiveness is not just 'forgetting' the past, but instead remembers it again and then forgives. In this process it is necessary to try to remember past facts and make honest moral judgments about past mistakes, injustices, and injuries. Forgiveness in the context of action politics does not mean freeing punishment against perpetrators of past crimes, but means free from acts of revenge . Forgiveness starts from an encouragement of 'moral judgment' and control of revenge.